2020
DOI: 10.1371/journal.pone.0230984
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GST- and P450-based metabolic resistance to pyrethroids on blood feeding in the major African malaria vector Anopheles funestus

Abstract: Insecticide resistance genes are often associated with pleiotropic effects on various mosquito life-history traits. However, very little information is available on the impact of insecticide resistance on blood feeding process in mosquitoes. Here, using two recently detected DNA-based metabolic markers in the major malaria vector, An. funestus, we investigated how metabolic resistance genes could affect the blood meal intake. After allowing both the field F1 and lab F8 Anopheles funestus strains to feed on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…RNAi knockdown of RproCYP4M1 increased the susceptibility and mortality of its nymphs subsequently exposed to deltamethrin (Paim et al, 2021). As a salivary protein, CYP6P9a is associated with feeding success and blood meal size of A. funestus (Nouage et al, 2020). TmCYP345C4, TmCYP307A1, TmCYP4BN60, and several other genes were highly or specifically expressed in salivary gland.…”
Section: Resultsmentioning
confidence: 99%
“…RNAi knockdown of RproCYP4M1 increased the susceptibility and mortality of its nymphs subsequently exposed to deltamethrin (Paim et al, 2021). As a salivary protein, CYP6P9a is associated with feeding success and blood meal size of A. funestus (Nouage et al, 2020). TmCYP345C4, TmCYP307A1, TmCYP4BN60, and several other genes were highly or specifically expressed in salivary gland.…”
Section: Resultsmentioning
confidence: 99%
“…RIMS-binding protein 2 is involved in neurotransmitter release and synaptic function [ 40 ], implying that it plays a potential role in neurophysiological changes associated with resistance. Glutathione S transferases, class Zeta, are part of the GST family, and several studies have demonstrated their role not only in insecticide detoxification processes but also in plasmodium infection in Anopheles and Aedes species [ 13 , 41 44 ]. Slit protein is involved in axon guidance and may play a role in resistance-related neuronal adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on insecticide resistance markers has shown an association between the CYP6P9a gene (a marker of cytochrome P450, which mediates metabolic resistance again pyrethroid insecticides) and the feeding success and blood meal size in An. funestus [ 59 ] . These findings highlight the need for further studies to improve knowledge of the influence of multiple insecticide resistance markers harbouring on the propensity of malaria vectors to blood feed.…”
Section: Discussionmentioning
confidence: 99%